Promoting Student Well-Being Through the SRA (Sekolah Ramah Anak) Program: Case Study In High School Level - Rahmia, Sovia Husni; Mutiani, Mutiani; Jumriani, Jumriani; Rusmaniah, Rusmaniah; Sari, Raihanah (The Innovation of Social Studies Journal, 2026)
The SRA (Sekolah Ramah Anak- Child-Friendly School) Program has been implemented in Indonesia for more than a decade as a national child protection–based education program in Indonesia. This study aims to examine how the SRA program is implemented in supporting students’ well-being. Used qualitative methods, data were collected from several high schools that have officially met the SRA standards through in-depth interviews, observations, and document analysis. The participants included school principals, teachers, and students who were directly involved in the implementation of the SRA program. The findings suggest that the implementation of the SRA program in SRA-standardized schools is shaped by everyday practices that emphasize awareness, trust, and teacher role modeling. Student awareness is developed through the application of positive discipline and the involvement of students in community-based activities and social projects, which encourage responsibility and empathy. Trust among school members is fostered by creating safe spaces for students, establishing whistleblowing systems for case reporting, and applying humane and non-punitive approaches in handling student-related issues without public shaming. Furthermore, teachers are perceived as central figures in SRA implementation by maintaining close relationships with students, demonstrating discipline, and modeling positive norms and behaviors in daily school life. These practices collectively contribute to the creation of a supportive school climate that enables students to feel safe, respected, and emotionally comfortable, thereby supporting student well-being within the SRA program.